Self-Assembling Injectable Hydrogel for Controlled Drug Delivery of Antimuscular Atrophy Drug Tilorone - Mohamed M. Abdelghafour; Ágota Deák; Tamás Kiss; Mária Budai-Szűcs; Gábor Katona; Rita Ambrus; Bálint Lőrinczi; Anikó Keller-Pintér; István Szatmári; Diána Szabó; László Rovó; László Janovák (Pharmaceutics, 2022)
A two-component injectable hydrogel was suitably prepared for the encapsulation and prolonged release of tilorone which is an antimuscular atrophy drug. The rapid (7–45 s, depending on the polymer concentration) in situ solidifications of the hydrogel were evoked by the evolving Schiff-base bonds between the aldehyde groups of modified PVA (4-formyl benzoate PVA, PVA-CHO, 5.9 mol% functionalization degree) and the amino groups of 3-mercaptopropionate chitosan (CHIT-SH). The successful modification of the initial polymers was confirmed by both FTIR and NMR measurements; moreover, a new peak appeared in the FTIR spectrum of the 10% w/v PVA-CHO/CHIT-SH hydrogel at 1647 cm−1, indicating the formation of a Schiff base (–CH=N–) and confirming the interaction between the NH2 groups of CHIT–SH and the CHO groups of PVA-CHO for the formation of the dynamic hydrogel. The reaction between the NH2 and CHO groups of the modified biopolymers resulted in a significant increase in the hydrogel’s viscosity which was more than one thousand times greater (9800 mPa·s) than that of the used polymer solutions, which have a viscosity of only 4.6 and 5.8 mPa·s, respectively. Furthermore, the initial chitosan was modified with mercaptopropionic acid (thiol content = 201.85 ± 12 µmol/g) to increase the mucoadhesive properties of the hydrogel. The thiolated chitosan showed a significant increase (~600 mN/mm) in adhesion to the pig intestinal membrane compared to the initial one (~300 mN/mm). The in vitro release of tilorone from the hydrogel was controlled with the crosslinking density/concentration of the hydrogel; the 10% w/v PVA-CHO/CHIT-SH hydrogel had the slowest releasing (21.7 h−1/2) rate, while the 2% w/v PVA-CHO/CHIT-SH hydrogel had the fastest releasing rate (34.6 h−1/2). Due to the characteristics of these hydrogels, their future uses include tissue regeneration scaffolds, wound dressings for skin injuries, and injectable or in situ forming drug delivery systems. Eventually, we hope that the developed hydrogel will be useful in the local treatment of muscle atrophy, such as laryngotracheal atrophy.